Resistance of upland rice to stem borer and its association with plant morphological characters - Martins, José Francisco da Silva; Tan, Nguyen Van; Pinheiro, Beatriz da Silveira (Pesquisa Agropecuaria Brasileira, 2014)
The association of plant morphological characters with the degree of damage caused by Diatraea saccharalis in rice varieties and breeding lines was studied. The percentage of attacked culms by this borer was directly correlated with plant height, with number and length of the internodes and with the internal and external diameters of the culm; on the other hand, this percentage was negatively correlated with tillering capacity. It was observed that hairy-leaf genotypes tended to suffer less damage. Among the genotypes studied, those considered traditional upland varieties were more damaged by stem borer than the introduced genotypes.